Short Total Synthesis of (+/-)--Lycorane by a Sequential Intramolecular Acylal Cyclisation (IAC) and Intramolecular Heck Addition Reaction - Monaco, Alessandra; Szulc, Blanka R.; Rao, Zenobia X.; Barniol-Xicota, Marta; Sehailia, Moussa; Borges, Bruno M. A.; Hilton, Stephen T. (Chemistry : a European journal, 2017)
An intramolecular acylal cyclisation (IAC) approach to the synthesis of a range of bicyclic heterocycles is reported. As an example of the utility of the IAC reaction, the methodology was applied in a protecting-group-free five-step total synthesis of (+/-)--lycorane, incorporating a new intramolecular Heck addition reaction to generate the pentacyclic core structure of the natural product in good yield.